A systematic review of antimicrobial peptides from fish with anticancer properties - Najm, Ahmed Abdulkareem; Azfaralarriff, Ahmad; Dyari, Herryawan Ryadi Eziwar; Syed Alwi, Sharifah Sakinah; Khalili, Nahid; Othman, Babul Airianah; Law, Douglas; Shahid, Muhammad; Fazry, Shazrul (Universiti Putra Malaysia Press, 2022)
Fish is a potential source of various forms of bioactive compounds. It can be used as a source of specific proteins, especially in medicine. Recently, studies related to the use of antimicrobial peptides (AMPs) from fish are being carried out to find an alternative cure for cancer. To achieve this objective, the AMP used must meet a condition where it possesses the ability to target tumor cells without affecting the normal cell. Therefore, this study aims to systematically review and classify the recent AMPs isolated from fish and their therapeutic activities, focusing on their anticancer and antimicrobial activities. A systematic review of studies published in English between 2017 and 2020 was conducted in PubMed NCBI, Biomed Central, Science Direct, and Google Scholar databases using keywords and inclusion and exclusion criteria. A systematic review conducted has identified 38 potential AMPs isolated from fish that have been reported to have antimicrobials activity. Of all of these, 21 AMPs also have anticancer properties. Therefore, it is important to continue to explore and study natural ingredients in developing new approaches in medicine. This research is essential to enable the potential of AMPs to be identified and applied.